Auslegung und Hermeneutik der Bibel in der Reformationszeit - Christ-von Wedel, Christine; Grosse, Sven (Historia Hermeneutica, 2017)
"The significance of the Bible for the Reformation is undisputed. Employing various perspectives, this volume reflects on biblical interpretation and hermeneutics during the time of the Reformation. It discusses the Wittenberg Reformers (Luther and Melanchthon) and the Reformed (including Bullinger, Calvin, and Bucer), along with their cross-connections to Erasmus, the Baptists, and the Christian reception of Jewish biblical interpretation."--
Keywords: Bible -- Criticism, interpretation, etc -- History -- 16th century; Bible -- Criticism, interpretation, etc -- Early works to 1800; Bible -- Hermeneutics -- History -- 16th century; Konferenzschrift -- 2014 -- Basel; Geschichte 1520-1560; Kontroverstheologie; Schriftverständnis; Reformation; Hermeneutik; Bibel; Reformierte Theologie; Lutherische Theologie; Exegese